Improvement of barrier properties of spray dried microparticles of iron and ascorbic acid by fluidized bed coating - Ferreira, M.A.; Nascimento, R.F.; Conti, A.C. [UNESP]; Kurozawa, L.E. (Elsevier, 2025)
Iron deficiency, linked to various diseases, is a global issue due to insufficient dietary intakes. Food fortification with iron and ascorbic acid is a common approach to address it. Microencapsulation of iron can minimize its oxidation, but spray drying can lead to low encapsulation efficiency and porous particles. To overcome these challenges, this study investigated two strategies: (i) combining protein with maltodextrin in the wall material to form a protein film on the microparticles surface and (ii) coating spray dried particles in a fluidized bed to improve protection of encapsulated compounds. Microparticles containing ferrous sulfate and ascorbic acid were produced by spray drying, using as wall materials the combination of whey protein isolate and maltodextrin in ratios of 0:100 (MP0), 30:70 (MP30), and 50:50 (MP50). Scanning electron microscopy revealed spherical particles with surface concavities. Encapsulation efficiency of ascorbic acid and Fe2+ ranged from 60.5 % (MP0) to 91.6 % (MP30) and from 13.2 % (MP50) to 49.7 % (MP30), respectively. MP30 microparticles exhibited better retention and protection properties of the active compounds and were selected for coating by fluidized bed with hydroxypropyl methylcellulose (1 %). The coated particles clusters (C-MP30) formed aggregates, characterized similarly to uncoated particles. Stability analysis under accelerated conditions (50 °C, 70 % relative humidity, 15 days) for MP30 and C-MP30 was carried out, analyzing water activity, ascorbic acid degradation, and Fe2+ oxidation. As results, C-MP30 particles had better initial stability, ensuring higher concentration of the compounds during the first days. However, the interaction between the coating and particle during the analysis resulted in increased degradation of the active compounds at the end of storage.